'Follow sourcing' and the transplantation and localization of Korean electronics corporations in northern Vietnam. Issue 4 (2nd October 2022) - Koo, Yangmi; Kim, Seonghun
ABSTRACT: This study examines the transplantation of clusters through 'follow sourcing' of Korean electronics industry transnational corporations (TNCs), their suppliers and individual actors in northern Vietnam, and the ways in which geographical and organizational proximity generate spillovers to local enterprises. Advanced manufacturing facilities, relationships with suppliers and training programmes give rise to direct and indirect learning and improvements in skills and technological capabilities. Transplanted clusters via follow sourcing and localization can serve as an intermediate stage between an externally controlled satellite cluster and an advanced cluster and they afford another latecomer development path to the Chinese model of 'obligated embeddedness'.